Benzylation of Benzene and Toluene with Benzylchloride over Clay-Based Acid Catalysts - Durap, Feyyaz; Akcay, Mehmet; Yurdakoc, Kadir (Asian Journal of Chemistry, 2010)
The pillared clay catalysts were calcined after in corporation of metal polycation ions with exchangeable cations and water. Friedel-Crafts alkylations of aromatic hydrocarbons were carried out in the presence of clay catalysts originating from bentonite. In these reactions, it has been found that pillared clays have excellent catalytic activity. It was found that iron pillared clay (Fe-PILC) was the more efficient catalyst producing quantitative conversion with greatly reduced amounts of catalysts in short reaction period. Their efficiency is attributed to the higher Fe3+, Cr3+ and Al3+ contents in the catalysts and pillaring effect. The clays have both Bronsted and Lewis acidities, which were determined by pyridine adsorptiondesorption and in situ FTIR technique.